ANALISIS HISTORI VISIBILITAS HILAL PERSPEKTIF ASTRONOMI MUSLIM ABAD PERTENGAHAN - Rustam, Rustam; Syarif, Muh. Rasywan (HISABUNA: Jurnal Ilmu Falak, 2026)
ABSTRACT Determining the beginning of the lunar month is crucial for Muslims, not only for religious observances such as fasting during Ramadan and the Hajj pilgrimage, but also for demonstrating the relationship between Islamic law and science. The crescent moon, as a marker of the beginning of the month, has been a key area of ​​study since the Middle Ages, when Islamic astronomy developed rapidly. This research addresses two sub-questions: the history of the concept of crescent moon visibility in the Middle Ages, and the methods of Muslim scientists and their implications for determining the beginning of the month in the Hijri calendar.This study aims to analyze the conceptual and methodological construction of crescent moon visibility in the works of medieval Muslim astronomers and examine its relevance to the theory of determining the beginning of the Hijri month in contemporary astronomical studies. This study uses a library research approach. Data are collected from classical and modern literature, then analyzed using historical, sharia, scientific, and philosophical approaches to explain the integration between empirical and normative aspects in determining the beginning of the Hijri month. This study finds that medieval Muslim scientists, such as Al-Battani, Al-Biruni, and Nashiruddin al-Tusi, have developed a systematic method of crescent moon observation by combining direct observation and mathematical calculations. The concept of imkanur rukyat, along with astronomical parameters such as lunar height, elongation, and age, form the basis for crescent moon visibility criteria. The implication of this research is that the thinking of medieval Muslim astronomers remains relevant to the development of modern astronomy. Their integration of sharia and astronomical aspects can serve as a foundation for refining methods for determining the beginning of the Hijri month.